Coupling Navier-Stokes and Cahn-Hilliard equations in a two-dimensional annular flow configuration - Vignal, P.; Sarmiento, A.; Côrtes, A.; Dalcin, L.; Calo, Victor (2015)
In this work, we present a novel isogeometric analysis discretization for the Navier-Stokes-Cahn-Hilliard equation, which uses divergence-conforming spaces. Basis functions generated with this method can have higher-order continuity, and allow to directly discretize the higherorder operators present in the equation. The discretization is implemented in PetIGA-MF, a high-performance framework for discrete differential forms. We present solutions in a twodimensional annulus, and model spinodal decomposition under shear flow.